2013
DOI: 10.1159/000348283
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value and Therapeutic Potential of TREM-1 in <b><i>Streptococcus pyogenes-</i></b>Induced Sepsis

Abstract: TREM-1 (triggering receptor expressed on myeloid cells) is a surface molecule expressed on neutrophils and macrophages which has been implicated in the amplification of inflammatory responses triggered during infection. In the present study, we have investigated the clinical significance of TREM-1 in Streptococcus pyogenes-induced severe sepsis in both experimentally infected mice as well as in patients with streptococcal toxic shock. We found that S. pyogenes induced a dose-dependent upregulation of TREM-1 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 33 publications
0
23
1
1
Order By: Relevance
“…However, blockage of TREM-1 signaling did not improve the survival of mice experiencing S. suis-induced septic shock in this study, which was inconsistent with the effects of TREM-1 blockage on sepsis or septic shock induced by other pathogens (33,34,45,(48)(49)(50). In contrast, activation of TREM-1 signaling with the agonistic antibody significantly improved the survival of mice infected with S. suis.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…However, blockage of TREM-1 signaling did not improve the survival of mice experiencing S. suis-induced septic shock in this study, which was inconsistent with the effects of TREM-1 blockage on sepsis or septic shock induced by other pathogens (33,34,45,(48)(49)(50). In contrast, activation of TREM-1 signaling with the agonistic antibody significantly improved the survival of mice infected with S. suis.…”
Section: Discussioncontrasting
confidence: 89%
“…Because of the central function of TREM-1 in amplification of the inflammatory response, TREM-1 was identified as an essential regulator of innate immunity in sepsis syndrome (35) and was confirmed as an attractive target for the treatment of septic shock (45,48), sepsis (30,33,34,49,50), inflammatory bowel disease (51,52), etc. However, blockage of TREM-1 signaling did not improve the survival of mice experiencing S. suis-induced septic shock in this study, which was inconsistent with the effects of TREM-1 blockage on sepsis or septic shock induced by other pathogens (33,34,45,(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, blockade of TREM-1 modulates the inflammatory response and improves survival in this and other mouse models of sepsis including CLP, and E. coli -, S. pyogenes -, or P. aeruginosa -induced peritonitis models [13, 2122, 4142, 61]. In this study, we demonstrated for the first time that a novel and first-in-class ligand-independent TREM-1 inhibitory peptide GF9 can be used to silence the TREM signaling pathway and prolong survival in mice with LPS-induced septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 TREM-1 activation was also shown to induce inflammatory mediators (CCL2, CCL3, IL6, TNF, Toll-like receptor [TLR] 2, and TLR4). [20][21][22] Soluble TREM-1 expression has recently been found to be a useful surrogate marker for sepsis. 23 The TREM-1 pathway has not been reported in patients with AD, despite the disease association with infection, 24,25 but increased TREM-1 expression has been recently reported in patients with psoriasis.…”
Section: Rna-seq Uncovers Novel Ad Biologymentioning
confidence: 99%